Operation Epic Fury vs. True Promise 4: A Political Economy Analysis of Competing Media Discourse in the US-Israel-Iran War - Hasan Shaikh (Journal of English Language Teaching, Linguistics, and Literature (JETLEE), 2026)
Media discourses in the US-Israel-Iran war serve not only as information dissemination but also as strategic tools of political economy. Thus, this study investigates the competing media discourses surrounding the 2026 US-Israel-Iran war, through the combined framework of CDA and the political economy of communication (PEC). Using a comparative corpus-based approach, the paper analyzes news reports and opinion articles published by Tehran Times and CNN between 28 February and 8 April 2026. The corpus consists of 301 articles from Tehran Times with 192205 tokens and 143 articles from CNN with 221754 tokens. The findings reveal that CNN primarily framed the conflict through security-centered and strategic narratives aligned with Western geopolitical interests, while Tehran Times constructed counter-hegemonic discourses emphasizing resistance, sovereignty, and anti-imperialist ideology. Through CDA model, the study demonstrates how linguistic choices and discursive practices reproduced broader social structures and power relations. Simultaneously, the PEC framework highlights the influence of ownership, ideology, and geopolitical alliances in shaping war reporting. However, to address the limitations of this study, future research can include multilingual, multimodal, and audience-centered analyses. Ultimately, the study argues that contemporary media discourse functions as a site of ideological struggle where global powers compete to define legitimacy, morality, and political reality in international conflicts.